ANALISIS KESENJANGAN SOSIAL DI SD N 06 KAYU AGUNG - Rizky, Muhammad; Indah Nur Aziza Alfatonah; Muhammad Aldri Putra Pratama (CV. KAMPUS AKADEMIK PUBLISING, 2024)
The purpose of this study is to analyze and describe the social gap that exists in SDN 06 Kayu agung along with its causes and solutions. The research method used is qualitative descriptive. The social situation is SDN 06 Kayu agung. The sampling technique is simple random sampling. The results showed social inequalities in various aspects such as facilities and infrastructure, access to education, economy and parenting.